A PRELIMINARY STUDY OF SMALL SCAVENGING CRUSTACEANS COLLECTED BY BAITED TRAPS IN A CORAL REEF OF BIDONG ISLAND, MALAYSIA - Nakajima, Ryota; Yoshida, Teruaki; Azman, B. A. R.; Yamazaki, Haruka; Toda, Tatsuki; Othman, B. H. R.; Zaleha, Kassim; Effendy, A.W.M. (Malaysian Journal of Science, 2013)
In order to examine small invertebrate scavenging fauna of tropical coral reef waters, baited traps were deployed in a coral reef of Bidong Island, Malaysia. The samples taken by the traps constituted only a single species of isopods (Cirolana sp.) and ostracods from three families (Cypridinidae, Cylindroleberididae, and Paradoxostomatidae). Cirolanid isopods were never collected in net-samples suggesting they are hyperbenthic scavenging species. Judging from its sheer numbers in the bait-attracted community (86.1-98.6%), cirolanid isopods are one of the most important small invertebrate scavengers in coral reef waters of Bidong Island. Abstrak Di dalam mengetahui kehadiran fauna invertebrat pemangsa di kawasan terumbu karang di perairan tropika beberapa perangkap berumpan telah diletakkan di sekitar kawasan terumbu karang di Pulau Bidong. Perangkap berumpan tersebut telah berjaya memerangkap hanya satu spesies tunggal isopod (Cirolana sp) dan juga tiga famili ostrakod (Cypridinidae, Cylindroleberididae, dan Paradoxostomatidae). Didapati, isopod cirolanid tidak pernah direkodkan kehadirannya di dalam mana-mana persampelan yang menggunakan net, menunjukkan bahawa Malaysian Journal of Science 32 (2): 59-66 (2013) 60 kumpulan organisma ini adalah sebagai spesies pemangsa hiperbentik. Merujuk kepada kehadirannya yg amat tinggi di dalam komuniti perangkap-berumpan tersebut (86.1-98.6%), didapati isopod cirolanid ini merupakan salah satu kumpulan invertebrate pemangsa kecil yang penting di kawasan terumbu karang di Pulau Bidong. (Keywords: Bait-trap, Cirolana isopods, Coral reef, Ostracods, Scavenger)